2017
DOI: 10.3390/ijms18020289
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of Vitamin D Receptor Affects an Immune Response in Primary Biliary Cholangitis via the VDR-miRNA155-SOCS1 Pathway

Abstract: Primary biliary cholangitis (PBC) is an immune-mediated cholestatic disease. Vitamin D receptor (VDR)-dependent signaling constrains an inflammatory response by targeting the miRNA155-SOCS1 (suppressor of cytokine signaling 1) axis. The VDR-miRNA155-SOCS1 pathway was investigated in the context of the autoimmune response associated with PBC. Human liver tissues from non-cirrhotic PBC (n = 22), cirrhotic PBC (n = 22), cirrhotic primary sclerosing cholangitis (PSC, n = 13), controls (n = 23), and peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…The importance of VDR expression in the development of other diseases is becoming increasingly apparent. Kempinska-Podhorodecka et al 20 showed that expression of the VDR gene in PBMCs of patients with primary biliary cirrhosis and primary sclerosing cholangitis is decreased. 20 Regarding the low expression of VDR gene in patients with BD, we could not find any significant association between methylation pattern and the expression level of VDR gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of VDR expression in the development of other diseases is becoming increasingly apparent. Kempinska-Podhorodecka et al 20 showed that expression of the VDR gene in PBMCs of patients with primary biliary cirrhosis and primary sclerosing cholangitis is decreased. 20 Regarding the low expression of VDR gene in patients with BD, we could not find any significant association between methylation pattern and the expression level of VDR gene.…”
Section: Discussionmentioning
confidence: 99%
“…Kempinska-Podhorodecka et al 20 showed that expression of the VDR gene in PBMCs of patients with primary biliary cirrhosis and primary sclerosing cholangitis is decreased. 20 Regarding the low expression of VDR gene in patients with BD, we could not find any significant association between methylation pattern and the expression level of VDR gene. More and larger studies on the molecular level are needed to determine the lower expression of VDR gene in patients with BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication of vitamin D-VDR signaling pathway has been studied in the PBC and PSC pathogenic process. Kempinska-Podhorodecka et al found that in PBC livers, either cirrhotic or not, there is a significant impairment in VDR expression, resulting in enhancement of non-coding miR155 and consequent SOCS1 reduction, which probably interferes with the negative feedback on pro-inflammatory cytokines response [275]. Actually, VDR is also an important receptor for ursodeoxycholic acid (UDCA) inducing cathelicidin expression in biliary epithelial cells [243]; it also mediates many epigenetic effects, which contribute to the reduction of pro-inflammatory cytokines synthesis [276].…”
Section: Vitamin D and Autoimmune Liver Diseasesmentioning
confidence: 99%
“…MiR-155, which is related to immune cell activation mainly through direct targeting of suppressor of cytokine signalling 1 (SOCS1), a well-known antagonist of inflammation, was also found to be overexpressed in PBC livers. 124 Finally, miR-34a and miR-132 were shown to be increased in the liver of cirrhotic patients with PBC when compared to healthy individuals, 125 which might be related with oxidative stress by direct targeting NRF2, and thus triggering disease progression.…”
Section: Mir-506 and Insp 3 Rmentioning
confidence: 99%